EFEKTIVITAS PENERAPAN APLIKASI SIMDA KEUANGAN DI KANTOR SEKRETARIAT DPRD KABUPATEN TANAH DATAR - putri dwi febria; Yasril Yunus; Nora Eka Putri (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2019)
This research focused on how effective the application of SIMDA Finance in DPRD Secretariat in assisting financial management and producing accurate, quality and timely financial reports. The effectiveness measurement indicators used in this research included program success, goal success, satisfaction with the program, and overall achievement of goals. This research was qualitative research with descriptive method. This research was conducted at the Tanah Datar DPRD Secretariat. Research informants were determined by Purposive techniques. Data in this research were collected through interview, observation and documentation study. The results of the study showed that, in general, the SIMDA application has been successfully implemented in the secretariat since 2009. This application was very effective because it simplified the financial management process and reports could be produced quickly and accurately. However, the effectiveness of its implementation in the DPRD Secretariat has not been maximized because there are still several inhibiting factors such as the large number of employees who could not operate SIMDA, the absence of special training on the use of SIMDA, the lack of availability of hardware and network disruptions that hinder the SIMDA operation